PENGARUH INVESTASI TEKNOLOGI INFORMASI TERHADAP EFISIENSI ORGANISASI - Arief Andani Hidayat; Didi Achjari (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2017)
The relationship between information technology (IT) investment and non-financial measures of organizations has been studied mostlyin the developed countries. These studies are mostly conducted in the context of banking, securities and manufacture sectors. Therefore, a study that examine the impact of IT investments in the context of developing countries and other sectors,such as higher educationwill be worth studied. The current study is empirically examined the relationship between IT investment and organizational efficiency in public sector. Eighteen Faculties within Universitas Gadjah Mada (UGM) which is one of the autonomous state owned universities in Indonesia have been used as sampel. Data were obtained from year 2013 to 2015. Data were analyzed using panel data regression. The result shows that IT investment positively affects efficiency in the entity.